The gender divide: Agents of change - Sarant, Louise (Nature (London), 2017)
The rights and roles of women in the kingdom are evolving as growing numbers pursue higher education in STEM subjects, at home and abroad. But, for Saudi Arabia's knowledge economy to really thrive, the ranks of women working in science must increase. The Nature Index spoke to five passionate researchers who have taken up the mantle.